Highly efficient fabrication of functional hepatocyte spheroids by a magnetic system for the rescue of acute liver failure. (March 2023) - Zhang, Jiabin; Xu, Yanteng; Zhuo, Chenya; Shi, Run; Wang, Haixia; Hu, Zuquan; Chan, Hon Fai; Kim, Hae-Won; Tao, Yu; Li, Mingqiang
Abstract: Engineering hepatocytes as multicellular cell spheroids can improve their viability after implantation in vivo for effective rescue of the devastating acute liver failure (ALF). However, there is still a lack of straightforward methods for efficient generation of functional hepatocyte spheroids. In this study, a magnetic system, consisting of magnetic microwell arrays and magnet blocks, is developed to realize magnetically controlled 3D cell capture and spatial confinement-mediated cell aggregation. The cell spheroids with smaller size show superior hepatic functions than the larger-sized counterparts. Notably, the intrinsic magnetism of magnetic microwell arrays can regulate superoxide anions in hepatocyte spheroids and herein promote various biological processes, including antioxidation, hepatocyte-related functions, and pro-angiogenic potential. Ectopic implantation of the functional cell spheroids in ALF-challenged mice significantly prolongs the animal survival, ameliorates inflammation, and promotes liver regeneration. Hence, application of the magnetic system for generation of functionally enhanced hepatocyte spheroids holds great potential for clinical translation in the future.